Strategi Kemampuan Public Speaking Remaja Childhood Trauma di MTsN 1 Palembang: Penelitian - Kgs.M.Abu Dzar Al-Ghifari; Fifi Hasmawati; Selvia Assoburu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This research is entitled “Public Speaking Skill Strategies for Adolescents with Childhood Trauma at MTsN 1 Palembang.” The purpose of this study is to identify the strategies applied in developing public speaking skills among adolescents who have experienced childhood trauma and to understand the factors that influence their self-confidence in speaking in public. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The subjects of this research are several students of MTsN 1 Palembang who have a history of childhood trauma experiences, as well as guiding teachers involved in the mentoring process.The results show that adolescents with childhood trauma tend to experience anxiety, fear of judgment, and a lack of self-confidence when speaking in front of others. However, through appropriate strategies such as emotional guidance, gradual training, supportive interpersonal approaches, and the application of relaxation techniques before speaking, the students showed improvement in their communication abilities and confidence to speak in public.In conclusion, the development of public speaking skills for adolescents with childhood trauma requires strategies that not only focus on the technical aspects of speaking but also on emotional recovery and the enhancement of psychological safety. An empathetic approach from teachers and the school environment plays an important role in building adolescents’ self-confidence to communicate effectively.